Analisis Strategi Bisnis Non Aeronautika PT Angkasa Pura I Bandara Internasional Syamsudin Noor Banjarmasin - Aldiefa, Athfal; Oktavianor, Tomi (Universitas Lambung Mangkurat, 2023)
This study aims to analyze the non-aeronautical business strategy of PT Angkasa Pura I at Syamsudin Noor Airport in Banjarmasin obtained from the identification of internal factor conditions (strengths and weaknesses) and external factors (opportunities and threats) and find the formulation of a non-aeronautical business strategy at PT Angkasa Pura I Airport Syamsudin Noor Banjarmasin. Identification of internal factors (strengths and weaknesses) and external factors (opportunities and threats) was obtained by researchers from the results of in-depth interviews with credible and experienced informants. Apart from that, external analysis was also obtained from PESTLE analysis on the non-aeronautical business environment. The research results from the identification and analysis of internal factors (strengths and weaknesses) and external factors (opportunities and threats) were processed with the Internal Factor Evaluation (IFE) matrix and the External Factor Evaluation (EFE) matrix. The formulation of the results of the IFE and EFE matrices is obtained from the results of the SWOT matrix. Finally, after processing the data through these matrices, we found a way to find out the right business strategy for the non-aeronautical business of PT Angkasa Pura I Syamsudin Noor Airport in Banjarmasin with the SPACE Strategy which interprets the company's position to be in the Cartesian coordinate quadrant. This study found that the non-aeronautical business of PT Angkasa Pura I Syamsudin Noor Airport in Banjarmasin is in a quadrant I position that can implement the strategy market penetration, market development, product development and diversification related and un related business. Keywords : Non Aeronautics, PESTLE, IFE Matrix, EFE Matrix, SWOT, SPACE Strategy Matrix